Factors Affecting the Integrity of Financial Statements - Novi Akhsani; Wiwit Setyawati; Nurbaeti Nurbaeti (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
This study examines the effects of audit committee, audit tenure, and financial distress on financial statement integrity in infrastructure companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Financial statement integrity is essential for ensuring the reliability, transparency, and credibility of corporate reporting, particularly in capital-intensive industries that require substantial external financing. Grounded in Agency Theory, this research investigates whether governance mechanisms, auditing characteristics, and financial conditions contribute to the quality of financial reporting. The study employed a quantitative approach using panel data obtained from 37 infrastructure companies over a five-year observation period, resulting in 185 firm-year observations. Data were analyzed using panel data regression with EViews 12. Model selection procedures, including the Chow, Hausman, and Lagrange Multiplier tests, identified the Random Effect Model as the most appropriate estimation method. The findings indicate that audit tenure has a significant negative effect on financial statement integrity, suggesting that prolonged auditor–client relationships may reduce auditor independence and professional skepticism. In contrast, audit committee and financial distress do not significantly influence financial statement integrity. Simultaneously, the independent variables significantly affect financial statement integrity, although the model demonstrates relatively low explanatory power. The study concludes that auditor independence remains a critical determinant of financial reporting integrity. These findings provide implications for regulators, auditors, and corporate management in strengthening governance practices and maintaining the credibility of financial statements.